HUBUNGAN BESAR UANG SAKU, FREKUENSI KONSUMSI FAST FOOD DAN PAPARAN IKLAN FAST FOOD DI MEDIA MASSA ELEKTRONIK DENGAN KEJADIAN GIZI LEBIH PADA REMAJA SMA MARTIA BHAKTI KOTA BEKASI TAHUN 2020 - Dita Afriyanti Puspita (2021)
More nutrition is one of the problems experienced by all age groups, one of which is adolescents. The prevalence of over nutrition in adolescents aged 16-18 years in Indonesia in 2018 was 9,5% and the prevalence in West Java province was 10,9%, in Bekasi City amounted to 11.28%. The purpose of this study was, to determine correlation between pocket money, fast food consumption and fast food advertising display in the electronic mass media with a high incidence of over nutrition in adolescents in Senior High School Martia Bhakti Bekasi city 2020. This study was an observational analytic study with a cross sectional design. The subjects in this study were students in grades 10, 11 and 12 aged 16-18 years and met the criteria of 55 respondents by means of sampling, namely stratified random sampling. Data for this research are obtained by anthropometry measurements for weight and height, questionnaires and food frequency questionnaire. Statistical calculations were performed using univariate, bivariate analysis with Chi-Square and Spearman Correlation tests and multivariate analysis using multiple logistic regression tests. The results of this study indicate that there is a significant relationship, moderate strength and a positive correlation between the amount of pocket money (p = 0,000, r = 0.499), the frequency of fast food consumption (p = 0.016, r = 0.380) and fast food advertising display in the electronic mass media (p = 0.014, r = 0.369) with a high incidence of over nutrition in adolescents in Senior High School Martia Bhakti Bekasi city 2020. The results of the multivariate analysis test showed that the variable of pocket money was the dominant factor in the incidence of overnutrition among adolescents at Senior High School Martia Bhakti Bekasi city 2020 (p = 0.000, OR = 33.313).